Motoric cognitive risk syndrome: Integration of two early harbingers of dementia in older adults - Semba, Richard D.; Tian, Qu; Carlson, Michelle C.; Xue, Qian-Li; Ferrucci, Luigi (Ageing research reviews, 2020)
[Display omitted] •Slow gait speed and subjective memory complaint are strong independent predictors of cognitive decline and dementia.•The motoric cognitive risk syndrome (MCR) integrates these two early harbingers of dementia.•Why older adults with MCR are at higher risk of dementia is not well understood.•Biomarkers associated with both low gait speed and subjective memory complaint provide clues into mechanisms underlying MCR.•Proteomics and metabolomics to may identify novel biomarkers, biological pathways, and therapeutic targets in MCR. Dementia is characterized by a long preclinical phase that may last years to decades before the onset of mild cognitive impairment. Slow gait speed and subjective memory complaint commonly co-occur during this preclinical phase, and each is a strong independent predictor of cognitive decline and dementia. Motoric cognitive risk (MCR) syndrome is a pre-dementia syndrome that combines these two early harbingers of dementia. The risk of cognitive decline or dementia is stronger for MCR than for either slow gait speed or subjective memory complaint alone. Slow gait speed and subjective memory complaint have several common risk factors: cardiovascular disease, diabetes mellitus, abnormal cortisol profiles, low vitamin D levels, brain atrophy with decreased hippocampal volume, and increased deposition of beta-amyloid in the brain. The underlying pathogenesis of MCR remains poorly understood. Metabolomics and proteomics have great potential to provide new insights into biological pathways involved in MCR during the long preclinical phase preceding dementia.